STRESSFUL WORK SITUATIONS FOR NURSES AT AN UNIVERSITY'S HOSPITAL - Isabella Saiki Navarro de Souza; Fabio José da Silva; Roseane Lins Vasconcelos Gomes; Iracema da Silva Frazão (Universidade Federal de Santa Maria, 2013)
http://dx.doi.org/10.5902/217976928322 Aim: to analyze stressful situations of nurses working in a university hospital. Method: cross-sectional study that used a part of a data bank from a master dissertation regarding the topic. The sample consisted of 73 nurses of a university hospital in the city of Recife, Pernambuco. Information about stressful work situations were collected through the summarized version of the Scale of Karasek (Job Stress Scale). For data analysis we used the chi-square test and Fisher exact test. Results: only the job sector had a statistically significant association with exposure to stressful situations (p-value = 0.05). Conclusions: obtained results suggest that nurses experience stressful work situations. However, it is recommended to conduct further studies to obtain more representative estimates, which explore occupational stress and other factors not addressed in this study.